MAPPING SOFT SKILLS IN MANAGEMENT ESP: A CONTENT ANALYSIS OF SYLLABUS INTEGRATION AND GAPS - Luluk Iswati; Abd. Rajab (University of Kuningan, 2026)
In the context of English for Specific Purposes (ESP) for management students, integrating soft skills into the curriculum has become increasingly essential. This study investigates the extent to which soft skills are embedded in an Intermediate Business English syllabus using a single-case qualitative content analysis. The analysis is guided by a predefined soft skills framework comprising five categories: communication, lifelong learning, teamwork, initiative, and problem solving. Document evaluation was conducted by a panel of seven experienced ESP teachers and triangulated with semi-structured interviews to enhance methodological credibility. The findings reveal that the syllabus strongly promotes verbal communication and demonstrates moderate integration of teamwork, initiative, and lifelong learning. However, aspects such as written communication, peer feedback, and open-ended critical thinking are underrepresented. Problem solving was identified as the weakest integrated skill. These results highlight the need to revise and enrich ESP syllabi to ensure balanced development of both language and essential soft skills. This study offers a detailed evaluative framework for examining soft skills integration in ESP curricula and provides practical implications for syllabus designers and educators seeking to align instructional practices with 21st-century workforce demands.